Pengetahuan Konten Pedagogis - Tina Sri Sumartini; Rostina Sunday; Sukanto Sukandar Madio; Ekasatya Aldila Afriansyah; Nita Puspitasasri; Reni Nuraeni; Irena Puji Lurytawati (Jurnal Pekemas, 2020)
A teacher's Pedagogical Content Knowledge (PCK) is important in implementing mathematics learning. Therefore it is necessary to do socialization about PCK to mathematics teachers. One of the efforts that can be done is to provide community service. This effort was carried out by holding workshops for mathematics teachers at Madrasah Aliyah Negeri 5 Cibatu. The data was collected by giving a questionnaire to the mathematics teacher. The results of this community service show that the development of PCK needs to be accompanied by the development of knowledge of mathematics content as an integral part of teacher competence in teaching mathematics.